Detection of single-base DNA mutations by enzyme-amplified electronic transduction - Patolsky, Fernando; Lichtenstein, Amir; Willner, Itamar (Nature biotechnology, 2001)
Here we describe a method for the sensitive detection of a single-base mutation in DNA. We assembled a primer thiolated oligonucleotide, complementary to the target DNA as far as one base before the mutation site, on an electrode or a gold–quartz piezoelectric crystal. After hybridizing the target DNA, normal or mutant, with the sensing oligonucleotide, the resulting assembly is reacted with the biotinylated nucleotide, complementary to the mutation site, in the presence of polymerase. The labeled nucleotide is coupled only to the double-stranded assembly that includes the mutant site. Subsequent binding of avidin–alkaline phosphatase to the assembly, and the biocatalyzed precipitation of an insoluble product on the transducer, provides a means to confirm and amplify detection of the mutant. Faradaic impedance spectroscopy and microgravimetric quartz-crystal microbalance analyses were employed for electronic detection of single-base mutants. The lower limit of sensitivity for the detection of the mutant DNA is 1 × 10 −14 mol/ml. We applied the method for the analysis of polymorphic blood samples that include the Tay–Sachs genetic disorder. The sensitivity of the method enables the quantitative analysis of the mutant with no PCR pre-amplification.